Evaluating Teach One Reach One – A Risk Reduction Intervention to Enhance Adult-Youth Communication about Sex and Reduce the Burden of HIV/STI - Dave, Gaurav (Am J Health Promot, 2016)
PURPOSE: Parents and caregivers play an important role in sexual socialization of youth, often serving as the primary source of information about sex. For African American rural youth who experience disparate rates of HIV/STI, improving caregiver-youth communication about sexual topics may help to reduce risky behaviors. This study assessed the impact of an intervention to improve sexual topic communication. DESIGN: Quasi-experimental, pre/posttest, controlled, community-based trial SETTING: Intervention was in two rural NC counties with comparison group in three adjacent counties. SUBJECTS: Participants (n=249) were parents, caregivers or parental figures for African American youth aged 10–14. INTERVENTION: Twelve-session curriculum for participating dyads. MEASURES: Audio-computer assisted self-interview to assess changes at 9 months from baseline in communication about general and sensitive sex topics and overall communication about sex. ANALYSIS: Multivariable models were used to examine the differences between the changes in mean of scores for intervention and comparison groups. RESULTS: Statistically significant differences in changes in mean scores for communication about general sex topics (p<0.0001), communication about sensitive sex topics (p<0.0001), overall communication about sex (p<0.0001) existed. Differences in change in mean scores remained significant after adjusting baseline scores and other variables in the multivariate models. CONCLUSIONS: In TORO, adult participants reported improved communication about sex, an important element to support risk reduction among youth in high prevalence areas.